Transcriptomic Analysis of the Activity of a Novel Polymyxin against Staphylococcus aureus - Jinxin Zhao (American Society for Microbiology, 2016)
ABSTRACT Polymyxin B and colistin are exclusively active against Gram-negative pathogens and have been used in the clinic as a last-line therapy. In this study, we investigated the antimicrobial activity of a novel polymyxin, FADDI-019, against Staphylococcus aureus. MIC and time-kill assays were employed to measure the activity of FADDI-019 against S. aureus ATCC 700699. Cell morphology was examined with scanning electron microscopy (SEM), and cell membrane polarity was measured using flow cytometry. Transcriptome changes caused by FADDI-019 treatment were investigated using transcriptome sequencing (RNA-Seq). Pathway analysis was conducted to examine the mechanism of the antibacterial activity of FADDI-019 and to rationally design a synergistic combination. Polymyxin B and colistin were not active against S. aureus strains with MICs of >128 mg/liter; however, FADDI-019 had a MIC of 16 mg/liter. Time-kill assays revealed that no S. aureus regrowth was observed after 24 h at 2× to 4× MIC of FADDI-019. Scanning electron microscopy (SEM) and flow cytometry results indicated that FADDI-019 treatment had no effect on cell morphology but caused membrane depolarization. The vancomycin resistance genes vraRS, as well as the VraRS regulon, were activated by FADDI-019. Virulence determinants controlled by SaeRS and the expression of enterotoxin genes yent2, sei, sem, and seo were significantly downregulated by FADDI-019. Pathway analysis of transcriptomic data was predictive of a synergistic combination comprising FADDI-019 and sulfamethoxazole. Our study is the first to examine the mechanism of the killing of a novel polymyxin against S. aureus. We also show the potential of transcriptomic and pathway analysis as tools to design synergistic antibiotic combinations. IMPORTANCE S. aureus is currently one of the most pervasive multidrug-resistant pathogens and commonly causes nosocomial infections. Clinicians are faced with a dwindling armamentarium to treat infections caused by S. aureus, as resistance develops to current antibiotics. This accentuates the urgent need for antimicrobial drug discovery. In the present study, we characterized the global gene expression profile of S. aureus treated with FADDI-019, a novel synthetic polymyxin analogue. In contrast to the concentration-dependent killing and rapid regrowth in Gram-negative bacteria treated with polymyxin B and colistin, FADDI-019 killed S. aureus progressively without regrowth at 24 h. Notably, FADDI-019 activated several vancomycin resistance genes and significantly downregulated the expression of a number of virulence determinants and enterotoxin genes. A synergistic combination with sulfamethoxazole was predicted by pathway analysis and demonstrated experimentally. This is the first study revealing the transcriptomics of S. aureus treated with a novel synthetic polymyxin analog.